STRATEGI PEMBELAJARAN MULTIPLE INTELLIGENCES PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMK AL BIRUNI BABAKAN CIWARINGIN CIREBON - Iim Imaniyah (Edulead : Journal of Education Management, 2020)
This thesis examines the Learning Strategies Based on Multiple Intelligence in Islamic Education Subjects at SMK Al Biruni. This research is a qualitative descriptive study. This study uses Howard Gardner's theory with M Quotle Intelligence and the theory of learning strategies according to Munif Chatib. The results showed that the learning preparation consisted of two stages, namely recognizing students' intelligence using TIMI (Interest Multiple Intelligences Test) and compiling a learning process plan. At the implementation stage the teacher carries out activities to provide perceptions and motivation and carries out activities based on Multiple Intelligences. These perceptions and motivations are in the form of alpha zone activities such as singing and doing reflection movements, Warmer by repeating the previous material, pre-teaching by providing an initial explanation of the course of the learning process, and scene setting by giving initial concepts to learning materials. Whereas in learning activities students are facilitated to learn through nine types of intelligence, namely: Verbal-Linguistic, Logical-Mathematical, Visual-Spatial, Physical-Kinesthetic, Musical-Rhythmic, Interpersonal, Intrapersonal, Naturalist and Existential-Spiritual not done at one time. Learning assessment is carried out authentically using three domains, namely; first cognitive with oral tests, written and assignments, second affective with observation, monthly targets and self-assessment, and third Psychomotor with assignments and practice. Abstrak Tesis ini mengkaji tentang Strategi Pembelajaran Berbasis Mutiple Intellegences Pada Mata Pelajaran PAI SMK Al Biruni. Penelitian ini merupakan penelitian deskriptif kualitatif. penelitian ini menggunakan teorinya Howard Gardner dengan Mutiple Intellegences dan teori strategi pembelajaran menurut Munif Chatib. Hasil penelitian menunjukkan bahwa persiapan pembelajaran terdiri atas dua tahapan,yaitu mengenali inteligensi siswa dengan menggunakan TIMI (Test Interest Multiple Intelligences) dan menyusun rencana proses pembelajaran. Pada tahap pelaksanaan guru melakukan kegiatan untuk memberikan apersepsi dan motivasi serta melakukan kegiatan-kegiatan berbasis Multiple Intelegences. Apersepsi dan motivasi tersebut berupa kegiatan alfa zona seperti bernyanyi dan melakukan gerakan refleksi,Warmer dengan mengulang materi sebelumnya, pre-teach dengan memberikan penjelasan awal jalannya proses pembelajaran,dan scene setting dengan pemberian konsep awal terhadap materi pembelajaran. Sedangkan dalam kegiatan pembelajaran siswa difasilitasi untuk belajar melalui kesembilan jenis kecerdasan, yaitu: Verbal-Linguistik, Logis-Matematis, Visual-Spasial, Jasmaniah-Kinestetik, Musikal-Berirama, Interpersonal, Intrapersonal, Naturalis Dan Eksistensial-Spritual tidak dilakukan dalam satu waktu. Penilaian pembelajaran dilakukan secara autentik dengan menggunakan tiga ranah yaitu; pertama kognitif dengan tes lisan, tertulis dan penugasan, kedua afektif dengan observasi, target bulanan dan penilaian diri, dan ketiga Psikomotorik dengan tugas dan praktek.